(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To investigate the characteristics of tongue diagnosis in patients with chronic hepatitis B at Le Van Thinh Hospital. Methods: A descriptive cross-sectional study was conducted from March to June 2024 on 395 patients with chronic hepatitis B at the Liver Clinic of Le Van Thinh Hospital, Thu Duc City, who agreed to participate. Tongue images were collected and analyzed using the ZMT-1A Tongue Analysis System. Results: Among the 395 patients surveyed, the main tongue features observed were a light red tongue body color (67.34%), normal tongue shape and size with thin or absent coating (59.24%), a predominance of white coating (53.16%), and moist coating in 80.76% of the cases. Statistically significant gender-based differences were found in blood stasis spots, tongue fissures, tongue papillae, and coating color, with p-values of 0.005, 0.010, and 0.036, respectively. Additionally, significant age-related differences were noted in coating color and thickness, both with p-values of 0.004. Conclusion: A light red tongue, normal size and shape, thin or absent coating, white coating color, and moist coating are common features in patients with chronic hepatitis B. Furthermore, gender is associated with differences in tongue papillae, blood stasis spots, and tongue fissures, while age influences variations in tongue coating color and thickness.